Three-Dimensional (3D) Printed Food Products From Halal Forensic Perspective: A Prelimenary Review - Ummu Hani Roslin; Mohd Ifwat Mohd Ghazali; Mohamed Faiz Asyraf Razali; Ahmad Syukran Baharuddin (USIM Press, 2024)
VOL. 10 NO. 1 (2022) Page (54-62)